What is the impact of intraperitoneal surfactant administration against postoperative intraabdominal adhesion formation? an experimental study - Pala, Sehmus; Kuloglu, Tuncay; Atilgan, Remzi; Ozkan, Zehra Sema; Hancer, Serhat (Tubitak Scientific & Technological Research Council Turkey, 2023)
Background/Aim: Surfactant is a surface-active substance that, in addition to its detergent effect, also has effects that reduce inflammation and fibrosis. Because of these effects, it was aimed herein to investigate the effect of intraperitoneal surfactant application on preventing postoperative peritoneal adhesion formation in a uterine horn adhesion model. Materials and methods: Twenty-one Wistar albino rats were randomly divided into 3 groups (G1-G3), as follows: G1 (n = 7): control group. The abdomen was opened and then closed; G2 (n = 7): adhesion group. The abdomen was opened. Then, a 2-cm linear incision was made over the right uterine horn, 2 mL of isotonic saline was administered intraperitoneally, and the abdomen was closed; and G3 (n = 7): treatment group. The abdomen was opened, a 2-cm linear incision was made over the right uterine horn, 2 mL (70 mg/kg) of surfactant was administered intraperitoneally, and the abdomen was closed. After 15 days, the rats were euthanized, the abdomens were reopened, and adhesion scoring was performed. After the right uterine horns were removed and fixed with 10% formalin, appropriate sections were taken from the traumatized tissue, stained with Masson's trichrome, and fibrosis and inflammation scoring were performed. Results: The adhesion area and intensity were significantly higher in G2 than in G1 and G3 (p = 0.001) and were similar in G1 and G3 (p = 0.165). While fibrosis and inflammation were significantly higher in G2 than in G1 and G3 (p = 0.001), there was no difference between G1 and G3 (p = 0.5). Conclusion: Intraperitoneal surfactant administration at a dose of 70 mg/kg was found to be effective in preventing intraabdominal adhesion formation in a rat uterine horn model.
Keywords: Postoperative adhesion; uterine horn; rat; surfactant; experimental model